2017
DOI: 10.1111/ene.13296
|View full text |Cite
|
Sign up to set email alerts
|

Principles of proportional recovery after stroke generalize to neglect and aphasia

Abstract: Our findings indicate that improvement from neglect or aphasia after stroke shows the same dichotomy and proportionality as observed in motor recovery. This is suggestive of common underlying principles of plasticity, which apply to motor and cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 9 publications
3
40
0
2
Order By: Relevance
“…These combined data increasingly point toward a symbiosis between upper limb and aphasia recovery. We agree with Marchi et al [1] that the chief importance behind their recent observations lies in the potential for more robust therapies. Nonetheless, we propose caution regarding statements of certainty that language improvement, while potentially synergistic with upper limb stroke recovery, can appropriately be evaluated using the proportional recovery rule.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These combined data increasingly point toward a symbiosis between upper limb and aphasia recovery. We agree with Marchi et al [1] that the chief importance behind their recent observations lies in the potential for more robust therapies. Nonetheless, we propose caution regarding statements of certainty that language improvement, while potentially synergistic with upper limb stroke recovery, can appropriately be evaluated using the proportional recovery rule.…”
supporting
confidence: 92%
“…The recent paper by Marchi et al ('Principles of proportional recovery after stroke generalize to neglect and aphasia') adds to an important dialogue regarding proportional recovery in post-stroke aphasia [1]. The authors concur with a seminal 2010 study by Lazar et al on the proportional recovery rule, defined as the maximum attainment of 70% recovery within a 3-month period from day 1 of stroke, predicted by initial impairment [2].…”
mentioning
confidence: 88%
“…When predicting behavioural performance in humans, these effect sizes are unprecedented. Like many of its counterparts 5,10,12 , this study also reported a group of 'non-fitters', who did not make the predicted recovery. But if non-fitters can be distinguished from fitters at the acute stage, as the authors' results also suggest, the implication is that we can predict most patients' recovery near-perfectly, at least during the first few months after stroke onset.…”
Section: Introductionmentioning
confidence: 54%
“…We found reason to suspect inflation in every study (apart from that by Feng and colleagues), which reported enough information for us to make the judgement. The most common reason why we could not make a judgement was when baselines were only related to recovery through multivariable models which included baseline scores 4,11,12 . But inflation in one variable's effect size will inflate the multivariable model's effect size as well: while we cannot estimate the magnitude of that inflation with any confidence for any particular model, we can predict that it's also there in those multivariable models.…”
Section: Re-examining Studies Of Proportional Recovery After Strokementioning
confidence: 99%
See 1 more Smart Citation